Real-time PCR-based Detection of Foodborne Pathogen Cronobacter sakazakii DNA in Infant Formula Milk with Specific Targeting on the hfq Gene - Nurjayadi, Muktiningsih; Juliansyah, Dandy Akbar; Declan, Jefferson Lynford; Putri, Gladys Indira; Krisdawati, Ismaya; Rahmawati, Atikah Nur; Azzahra, Maharanianska; Maulana, Irvan; Putri, Gusti Angieta; Kurniadewi, Fera; Kartika, Irma Ratna; Saamia, Vira; et al. (HAYATI Journal of Biosciences, 2025)
Cronobacter sakazakii has been linked to cause meningitis, necrotizing enterocolitis, and sepsis in infants and newborns, with case fatality rates ranging from 40 to 80%. The most common source of infection has been identified as Cronobacter sakazakii-contaminated infant formula. With a relatively specific target hfq gene, this study aims to develop a real-time PCR method to identify Cronobacter sakazakii in infant formula milk. Real-time PCR is used as a detection method because rt- PCR has higher specificity and sensitivity compared to conventional PCR methods. The real-time PCR method also has a higher level of effectiveness and time efficiency compared to conventional PCR. Cronobacter sakazakii ATCC 29544 genomic DNA was isolated and used in a real-time PCR assay. Cronobacter sakazakii DNA was amplified using a primer targeting the hfq gene, yielding a 145 bp amplicon. The results of the real-time PCR test showed that Cronobacter sakazakii DNA with a concentration of 53 ng/µL could be amplified by the primer pairs of hfq gene with Ct values of 11 respectively then had Tm values of 81.7°C±0.5. The specificity test showed that the hfq primer pairs could differentiate between the target and some non-target bacteria. The sensitivity test showed the ability of the primer to detect the smallest concentration of 3.392 pg/µL with a Ct of 26.16. Based on the results obtained, it can be concluded that the hfq primer has the potential to be used as a fast detection method for Cronobacter sakazakii bacteria in infant formula using real-time PCR.